Arşiv belgeleriyle Ermeni faaliyetleri, 1914-1918 (Ankara Ankara Ankara Ankara Ankara)
9 cilt (1. c. xi, 717 sayfa ; 2. c. vii, 653 sayfa ; 3. c. viii, 714 sayfa ; 4. c. viii, 742 sayfa ; 5. c. viii, 605 sayfa ; 6. c. viii, 557 sayfa ; 7. c. xi, 713 sayfa ; 8. c. xi, 595 sayfa ; 9. c. iii, 253 sayfa)